Effectiveness of Administration Staff Performance - Niswaty, Risma; Samaun, Nurlaila; Saleh, Sirajuddin (Universitas Negeri Makassar, 2023)
. Effectiveness is the relationship between output and objectives or it can also be said to be a measure of the level of output. Effectiveness is also often used to measure the success achieved by an organization or company in relation to planned programs. This research aims to determine the effectiveness of the performance of administrative employees at SMK Negeri 1 Makassar. This research used qualitative methods with 5 (five) informants, namely the school principal, the head of administration, and employees in the administration sector. This research was conducted at SMK Negeri 1 Makassar. The data collection techniques used were observation, interviews, and documentation. The data analysis that will be used in this research is data collection reduction, data presentation, data condensation, and conclusions. The results of the research show that the effectiveness of the performance of administrative staff at SMK Negeri 1 Makassar is quite effective, in other words, the performance of administrative staff is seen through quality, quantity, discipline, politeness, responsibility, knowledge, skills, and work evaluation. Problems related to the work results of administrative employees in carrying out their duties, these factors can be used as a benchmark in conducting an assessment of an employee's performance level even though it is realized that employee performance is not the only factor that can determine success in achieving this. However, there are still aspects that have not been implemented optimally. Based on these findings, it is recommended that administrative staff increase their responsibility towards fellow administrative staff and employees.